Retail Learning Through Self Efficacy as An Intervening Variable to Improve Work Readiness of Students - Ni'am, Minhajun; Sulistyowati, Raya (Economic Education Analysis Journal, 2024)
This study was conducted to determine the effect of retail learning on students through self-efficacy as an intervening variable to improve students' work readiness. This research uses quantitative methods. The population in the study were 12th grade students of Business Online Marketing (BDP) SMKN 10 Surabaya. In this study, through the Slovin formula, the sample in this study was 102 students and used purposive sampling. The criteria for respondents in this study were 12th grade Business Online Marketing (BDP) students, internships in retail and retail learning at school. The data collection technique used in this research used questionnaires, interview and documentation. Data analysis using SmartPLS software through three stages, namely internal model analysis, external model analysis, and hypothesis testing. The results showed that retail learning has a positive and significant effect on work readiness. Retail learning has a positive and significant effect on self-efficacy. self-efficacy has a significant positive and significant effect on work readiness. Retail learning through self-efficacy can mediate student work readiness.